Persistence of coronary risk factor status in participants 12-18 months following percutaneous coronary intervention - Fernandez, R.; Griffiths, R.; Juergens, C.; Davidson, Patricia; Salamonson, Y. (Lippincott Williams and Wilkins, 2006)
Background: Percutaneous coronary intervention (PCI) is a widely performed revascularization technique for coronary heart disease; however, there is limited research investigating the risk factor status of patients 1 year after the procedure. Objective: This cross-sectional study was conducted to investigate the self-reported risk factor status by patients who had undergone a PCI at a major teaching hospital in Sydney, Australia.Subjects: Two hundred seventy participants who underwent PCI between April 2003 and March 2004 and who met the inclusion criteria were followed up 1 year after the PCI. Methods: After obtaining informed consent, a follow-up self-administered questionnaire was mailed to participants. Information was collected relating to the following coronary risk factors: smoking, and physical activity status, blood pressure and cholesterol levels, body mass index, depression, anxiety, and stress levels. Results: Two hundred two participants (75%) returned a completed questionnaire. Approximately one third of participants had at least two modifiable risk factors. The most common cardiovascular risk factors identified were physical inactivity, increased body mass index, high blood pressure, and high cholesterol. Approximately half the women (46%) and a quarter of the men had at least two modifiable risk factors. Only a minority (11%) of the participants continued to smoke at 1-year follow up. Participating in physical activity for a total time of 150 minutes or more per week was reported by only 42% of the participants. Depression and anxiety were present in 25% and stress in 17% of the participants. A third of the participants (n = 64) erroneously believed that they had no heart problems. Conclusions: The findings reveal inadequate management of modifiable risk factors among post-PCI participants 12 to 18 months after revascularization, which highlights a need for tailored secondary prevention interventions to address factors contributing to cardiovascular risk. The evidence obtained from this study will inform the development of an intervention to address cardiovascular risk factor modification.